Dark networks and corruption: uncovering the offshore industry - Almeida, Lucas da Silva (2017)
Among the many social structures that cause inequality, one of the most jarring is on the use of loopholes to both launder money and evade taxation. Such resources fuel the \"offshore finance\" industry, a multi-billion dollar sector catering to many of those needs. These run under the logic of \"Dark Networks\" avoiding detection and oversight as much as possible. While there are legitimate uses for offshore services, such as protecting assets from unlawful seizures, they are also a well documented pipeline for money stemming from ilegal activities. These constructs display a high amount of adaptiveness and resilience and the few studies done had to use incomplete information, mostly from local sources of criminal proceedings. This work is to analyzes the network of offshore accounts leaked under the Panama Papers report by the International Consortium of Investigative Journalists. This registers the activities of the Mossack Fonseca law firm in Panama, one of the largest in the world on the Offshore field. It spans over 50 years and provide us with one of the most complete overview thus far of how these activities are connected, the topology of such network and what it displays in resilience against attempts to target this scheme